EIF2α phosphorylation: a hallmark of both autophagy and immunogenic cell death. (2nd September 2020) - Humeau, Juliette; Bezu, Lucillia; Kepp, Oliver; Kroemer, Guido
ABSTRACT: Different intrinsic and extrinsic stress pathways including endoplasmic reticulum (ER) stress converge on the phosphorylation of eukaryotic translation initiation factor 2A (EIF2A, best known as eIF2α), which characterizes the so-called "integrated stress response". This phosphorylation event is important for the induction of autophagy in response to multiple distinct stressors, as well as for the exposure of calreticulin (CALR) as an "eat me" signal on the surface of the plasma membrane of stressed cells. Both autophagy and CALR exposure are required for immunogenic cell death, a modality of cellular demise that ignites anticancer and antiviral immune responses. In several different cancer types, eIF2α phosphorylation indicates favorable prognosis, correlating with an enhanced antitumor immune response.